"The Inevitable Products of Racial Segregation": Multigenerational Consequences of Exclusionary Housing Policies on African Americans, 1910–1960. (29th October 2018) - Woods, Louis Lee
Abstract: From 1910 to 1960, whites fought viciously and persistently to prevent African Americans from living in decent housing in racially integrated neighborhoods. In 1910, Baltimore was the first city to adopt an ordinance banning African Americans from white neighborhoods. In part, this law was justified as a means to restrain the violent behavior of white citizens who might otherwise act as vigilantes against their black neighbors. Other cities followed suit. These racial zones were declared unconstitutional by the U.S. Supreme Court. However, for 31 years this Court sanctioned the adoption of private restrictive covenants that were effective at blocking African Americans from buying or renting a house in a white neighborhood. In the 1930s, the insertion of racially restrictive covenants became both a protective mechanism and a prerequisite for federal mortgage lending, insurance, and guarantees by a variety of national housing agencies. In effect, the federal government enforced racial segregation even though local governments were not allowed to. The net effect of three decades of federal housing programs was to drive an economic wedge between federally subsidized housing for whites and federally enforced denial of housing loans in African American neighborhoods. Those policies made whites wealthy at the expense of African Americans, a condition that still persists and will continue to do so in the absence of federal intervention to reverse the wealth gap it helped to create.